Student's naturalist intelligence in studying high plant botanicals by inquiry model - Dharmono Dharmono; Atika Rahmawati (JURNAL BIOEDUKATIKA, 2019)
Naturalist intelligence was the expertise in recognizing and classifying various species of flora and fauna from an individual environment. The principle of learning of Plant Botany in higher education was the application of the process of observing, measuring, testing, estimating, analyzing, comparing, classifying, experimenting and making conclusions by applying the principle of learning by doing. Therefore naturalist intelligence was very necessary. This study aims to determine the naturalist intelligence of students in the High Plant Botany course. This study uses a quantitative descriptive approach with the Action Research model Inquiry method. The study was conducted on 40 students of high plant botany Biology Education Subjects PMIPA Department FKIP Lambung Mangkurat University with 12 practicums as many times as measurements (1st practicum Cycadopsida Class, 6 Class Magnoliopsida practicum and 12 Liliopsida Class labs). The character of naturalist intelligence was measured using student worksheets which include; 1) Sensitivity to plants, 2) Expertise in differentiating members of plant species, 3) Ability to recognize the existence of plant species, and 4) Ability to map relationships between several plant species. Data were analyzed descriptively. The results of the study showed that there was a tendency to decrease the value of students' naturalist intelligence in high plant botany courses from repeated observations made. Based on the categories in a row with a high category (grades 75.6-90.5) as many as 21.3% of students, medium category (grades 60.6-75.5) as many as 76.6% students, and low categories (grades 40, 6-60.5) as many as 3.1% of students.